2018
DOI: 10.5713/ajas.17.0657
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of phytogenics in chickens and pigs — A review

Abstract: Environmental stressors like pathogens and toxins may depress the animal immune system through invasion of the gastrointestinal tract (GIT) tract, where they may impair performance and production, as well as lead to increased mortality rates. Therefore, protection of the GIT tract and improving animal health are top priorities in animal production. Being natural-sourced materials, phytochemicals are potential feed additives possessing multiple functions, including: anti-inflammatory, anti-fungal, anti-viral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 107 publications
1
59
0
Order By: Relevance
“…As a pro-inflammatory cytokine, IL-1ß mediates many pathways involved in apoptosis or inflammation [31]. It is well-known that S. cerevisiae and A. oryzae cell wall are rich in β-glucans [3], which can inhibit IL-1ß production [32] and thereby reduce NF-κB-mediated inflammatory responses [33]. Therefore, IL-1ß is positively correlated with NF-κB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a pro-inflammatory cytokine, IL-1ß mediates many pathways involved in apoptosis or inflammation [31]. It is well-known that S. cerevisiae and A. oryzae cell wall are rich in β-glucans [3], which can inhibit IL-1ß production [32] and thereby reduce NF-κB-mediated inflammatory responses [33]. Therefore, IL-1ß is positively correlated with NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is a main inflammatory factor, which promotes reactive nitrogen species (RNS) content [11]. In normal conditions, NF-κB binds with the inhibitory protein named inhibitor of kappa B (IκB) and has no effect [33]. With stimulants such as heat stress or infection, IκB phosphorylates and releases the NF-κB as a nuclear transcription factor to induce an inflammatory response [33].…”
Section: Discussionmentioning
confidence: 99%
“…These are responsible for triggering elements of the cell's defense system, such as superoxide dismutase (SOD), catalase (CAT), glutathione reductase (Gr), and haem oxygenase-1 (HO-1), to raise the cell's resistance to stress. According to our previous studies, phytochemicals from various plant materials exerted free radical scavenging effects and the ability to upregulate Nrf2 expression to further trigger downstream antioxidant mRNA expression, which had suggested that the plant materials could serve as natural antioxidants to solve the issue of oxidative stress in the poultry industry Lin et al 2017;Huang and Lee 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the interleukin-6 (IL-6) and signal transducer and activator of transcription factor-3 (STAT3) signaling pathway have been studied and IL-6, a phosphorylated glycoprotein, is a major causative factor which plays an important role in inflammatory disease [6,7]. IL-6 plays an important role in anti-inflammatory and host defense and overexpression of IL-6 due to pathogens, stresses, and aging may lead to the pathogenesis of inflammatory processes, autoimmune response, and cancer [8][9][10]. The therapeutic antibody (Ab) agents which inhibit IL-6 have been developed and showed effective and potential alternatives for inflammatory diseases refractory to conventional drugs.…”
Section: Introductionmentioning
confidence: 99%